Assessment of Nurses’ Knowledge Regarding Breast Cancer at Primary Health Care Centers in Al-Sader District - Okab , Ammar A (Diyala Journal of Medicine, 2019)
Background: Breast cancer is the most common, prevalent and diagnosed that affects women and the leading cause of death and disability worldwide and is a leading cause of morbidity and mortality among women. Objective: To assess the levels of knowledge among nurses regarding breast cancer at primary health care centers in Al-Sader district and to find out the relationship between socio- demographic characteristic and levels of knowledge. Patients and Methods: A cross-sectional study in which assessment approach is applied to achieve objectives of study, The period of the study was from 2nd July 2017 to 28th May 2018. The sample was non-probability (purposive sample) of 50 nurses who working at primary health care centers in Al-Sader district and selected according to criteria of sample and for the purpose of the study. A questionnaire used was consist of (37) items which was distributed across (2) main parts which are the socio-demographic characteristics which included (7) items, to assess levels of knowledge regarding the breast cancer these comprised (30) items. Data analysis by using program of SPSS version 20. Descriptive data through determination of: frequencies, percentages and mean of score to measure the level of knowledge to nurses. Inferential statistical data analysis by application Chi –square test used this for determine the association between the nurse’s socio-demographic characteristics and knowledge of nurses about breast cancer. Results: Results of the study that more than half of nurses with good levels of knowledge regarding breast cancer and there are significant association between sources of information and knowledge of nurses regarding breast cancer. Conclusion: That establish specially heath educational programs that provide information about breast cancer to the community.